Răspuns :
100 - [ 250 - 5 ×(X - 5) : 5 ] x 3 = 40
[ 250 - 5 ×(X - 5) : 5 ] x 3 =100 - 40
[ 250 - 5 ×(X - 5) : 5 ] x 3 = 60
250 - 5 ×(X - 5) : 5 = 60 : 3
250 - 5 ×(X - 5) : 5 =20
5 ×(X - 5) : 5 = 250 - 20
5 ×(X - 5) : 5 =230
X - 5 = 230 ×5 : 5
X - 5 = 230
X = 230 + 5
X = 235
643 - [( x - 162 ) : 5 + 159 ] = 454
( x - 162 ) : 5 + 159= 643 - 454
( x - 162 ) : 5 + 159= 189
( x - 162 ) : 5 = 189 - 159
( x - 162 ) : 5 = 30
x - 162 = 30 × 5
x - 162 = 150
x = 150 + 162
x = 312
[(3 × X + 4 )× 2 + 5 ] × 3 + 5 = 170
[(3 × X + 4 )× 2 + 5 ] × 3 = 170 - 5
[(3 × X + 4 )× 2 + 5 ] × 3 = 165
(3 × X + 4 )× 2 + 5 = 165 : 3
(3 × X + 4 )× 2 = 55 - 5
(3 × X + 4 )× 2 = 50
3 × X + 4 = 50 : 2
3 × X + 4 = 25
3 × X = 25 - 4
3 × X = 21
X = 21 : 3
X = 7
[ 250 - 5 ×(X - 5) : 5 ] x 3 =100 - 40
[ 250 - 5 ×(X - 5) : 5 ] x 3 = 60
250 - 5 ×(X - 5) : 5 = 60 : 3
250 - 5 ×(X - 5) : 5 =20
5 ×(X - 5) : 5 = 250 - 20
5 ×(X - 5) : 5 =230
X - 5 = 230 ×5 : 5
X - 5 = 230
X = 230 + 5
X = 235
643 - [( x - 162 ) : 5 + 159 ] = 454
( x - 162 ) : 5 + 159= 643 - 454
( x - 162 ) : 5 + 159= 189
( x - 162 ) : 5 = 189 - 159
( x - 162 ) : 5 = 30
x - 162 = 30 × 5
x - 162 = 150
x = 150 + 162
x = 312
[(3 × X + 4 )× 2 + 5 ] × 3 + 5 = 170
[(3 × X + 4 )× 2 + 5 ] × 3 = 170 - 5
[(3 × X + 4 )× 2 + 5 ] × 3 = 165
(3 × X + 4 )× 2 + 5 = 165 : 3
(3 × X + 4 )× 2 = 55 - 5
(3 × X + 4 )× 2 = 50
3 × X + 4 = 50 : 2
3 × X + 4 = 25
3 × X = 25 - 4
3 × X = 21
X = 21 : 3
X = 7